A need for standardized reporting of introgression: Insights from studies across eukaryotes. Issue 5 (1st October 2022) - Dagilis, Andrius J.; Peede, David; Coughlan, Jenn M.; Jofre, Gaston I.; D'Agostino, Emmanuel R. R.; Mavengere, Heidi; Tate, Alexander D.; Matute, Daniel R.
Abstract: With the rise of affordable next‐generation sequencing technology, introgression—or the exchange of genetic materials between taxa—has become widely perceived to be a ubiquitous phenomenon in nature. Although this claim is supported by several keystone studies, no thorough assessment of the frequency of introgression across eukaryotes in nature has been performed to date. In this manuscript, we aim to address this knowledge gap by examining patterns of introgression across eukaryotes. We collated a single statistic, Patterson's D, which can be used as a test for introgression across 123 studies to further assess how taxonomic group, divergence time, and sequencing technology influence reports of introgression. Overall, introgression has mostly been measured in plants and vertebrates, with less attention given to the rest of the Eukaryotes. We find that the most frequently used metrics to detect introgression are difficult to compare across studies and even more so across biological systems due to differences in study effort, reporting standards, and methodology. Nonetheless, our analyses reveal several intriguing patterns, including the observation that differences in sequencing technologies may bias values of Patterson's D and that introgression may differ throughout the course of the speciation process. Together, these results suggest the need for a unified approach to quantifying introgression in natural communities and highlight important areas of future research that can be better assessed once this unified approach is met.